2008
DOI: 10.1073/pnas.0802345105
|View full text |Cite
|
Sign up to set email alerts
|

Bves directly interacts with GEFT, and controls cell shape and movement through regulation of Rac1/Cdc42 activity

Abstract: Bves is an integral membrane protein with no determined function and no homology to proteins outside of the Popdc family. It is widely expressed throughout development in myriad organisms. Here, we demonstrate an interaction between Bves and guanine nucleotide exchange factor T (GEFT), a GEF for Rho-family GTPases. This interaction represents the first identification of any protein that has a direct physical interaction with any member of the Popdc family. Bves and GEFT are shown to colocalize in adult skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 58 publications
5
86
0
Order By: Relevance
“…a n for these characteristics does not add up to total studied (n ¼ 557) because of missing information. Cancer Researchp63RhoGEF, an important Gaq effector, has been reported to mediate RhoA, Rac1, or Cdc42 activation in different cell types (35,41,42). Our data showed that GPR116 mediated RhoA and Rac1 activation by Gaq and p63RhoGEF signaling.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…a n for these characteristics does not add up to total studied (n ¼ 557) because of missing information. Cancer Researchp63RhoGEF, an important Gaq effector, has been reported to mediate RhoA, Rac1, or Cdc42 activation in different cell types (35,41,42). Our data showed that GPR116 mediated RhoA and Rac1 activation by Gaq and p63RhoGEF signaling.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, p63Rho-GEF/GEFT has been reported to activate Rac1 and mediate tumorigenesis, tumor metastasis, and myogenesis (8,35,36). To investigate whether p63RhoGEF is required for the activation of RhoA and Rac1 in breast cancer cells, we overexpressed p63RhoGEF in MDA-MB-231 cells.…”
Section: Regulation Of Rhoa and Rac1 Activity By Gpr116 Is Through P6mentioning
confidence: 99%
“…Because uterine luminal epithelial transformation involves dynamic reorganization of the actin cytoskeleton, 28 and that Rac1 has been shown to be involved in orchestrating cell shape remodeling, 20,21,29 we speculated that uterine Rac1 deficiency would impair the functional integrity of the luminal epithelia at periimplantation. Indeed, electron microscopy analysis revealed a dramatic cell shape difference between the Claudin 7 was comparably expressed in the basolateral surface in both WT and Rac1 null epithelium, its prominent expression in the apical membrane of epithelial cells disappeared in the absence of uterine Rac1 (Figure 4g).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from ion channels and pumps, it is pos- sible that Popdc also interacts with proteins involved in channel oligomerization or membrane trafficking. VAMP2/3 and GEFT are 2 proteins that have been shown to interact with Popdc1 (47,48). VAMP2/3 has been shown to be involved in membrane vesicle fusion and could be involved in ion channel trafficking.…”
Section: Discussionmentioning
confidence: 99%